COVID-19 epidemic: Exercise or not to exercise; That is the question! - Halabchi, F.; Ahmadinejad, Z.; Selk-Ghaffar, M. (Asian Journal of Sports Medicine, 2020)
In December 2019, a public health emergency was induced by an outbreak of novel beta coronavirus termed 2019-novel coronavirus (SARS-CoV-2) in Wuhan City, Hubei Province, China, which is going to be a worldwide epidemic with high mortality and morbidity (1, 2). In the time of writing this editorial (March 10, 2020), more than 100000 persons from more than 100 countries have been infected with more than 4000 deaths reported. Clinical manifestations of COVID-19 consist of fever, cough, dyspnea, myalgia, headache and diarrhea (3). Fatal pulmonary involvement and multi-organ failure has occurred in a portion of infected individuals (4). The virus is an enveloped RNA coronavirus which is mainly transmitted from person-to-person respiratory spread (people who are in close contact with each other or respiratory droplets produced when an infected person coughs or sneezes) and to a lesser extent from contact with contaminated surfaces or objects (1, 2). Preventive strategies may efficiently limit the rapidly expanding outbreaks of 2019-nCoV, globally (5).